2023
DOI: 10.3390/info14020086
|View full text |Cite
|
Sign up to set email alerts
|

Universal Learning Approach of an Intelligent Algorithm for Non-GNSS Assisted Beamsteering in V2I Systems

Abstract: In intelligent transportation systems, an important task is to provide a highly efficient communication channel between vehicles and other infrastructure objects that meets energy efficiency requirements and involves low time delays. The paper presents a method for generating synthetic data of the “vehicle-to-infrastructure” system, capable of simulating many scenarios of traffic situations to increase the generalizing ability of an intelligent beamsteering algorithm. The beamsteering algorithm is based on gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The authors suggested a systematic approach to structure and tailor the IoT protocol stack, making it easier to identify areas for adjustment and optimization. In the work by Lopukhova et al [24], a smart beam-steering algorithm was presented, leveraging vehicle positioning data. This algorithm enhances the generalization capability of the employed machine learning (ML) algorithm, mitigating the impact of the received signal power parameters on system performance and bolstering the system's resilience against multipath propagation.…”
Section: V2imentioning
confidence: 99%
“…The authors suggested a systematic approach to structure and tailor the IoT protocol stack, making it easier to identify areas for adjustment and optimization. In the work by Lopukhova et al [24], a smart beam-steering algorithm was presented, leveraging vehicle positioning data. This algorithm enhances the generalization capability of the employed machine learning (ML) algorithm, mitigating the impact of the received signal power parameters on system performance and bolstering the system's resilience against multipath propagation.…”
Section: V2imentioning
confidence: 99%
“…SUMO offers capabilities for constructing, adjusting, and modeling custom traffic flow architectures and supporting tools for importing network and ODMs of existing route sections. SUMO's versatility enables the study of traffic control strategies and vehicular communication systems [27]. The high-detail simulation in SUMO is essential for analyzing and optimizing traffic management strategies, evaluating the impact of infrastructure modifications, and examining vehicle interactions in complex urban environments [28].…”
Section: Implementation Of Intelligent Transport Systems Via Simulati...mentioning
confidence: 99%
“…It required us to develop an approach to reducing this discrepancy in datasets, which is the topic of this paper. In our previous work [27], we showcased an application of ML in ITSs focusing on specific traffic flow data, based on which the location of the "connected car" was determined to generate a dedicated radio channel, tuning the phased antenna array radiation pattern. The approach involved generating synthetic data to train the ML algorithm within the V2I system, leveraging the SUMO simulation model and the Longley-Rice propagation model [87].…”
Section: Capturing Intelligent Transport System Data To Develop Machi...mentioning
confidence: 99%
See 2 more Smart Citations